Contesting the Gothic : fiction, genre and cultural conflict, 1764-1832 - Watt, James (Cambridge University Press, 1999)
Charting its vicissitudes from Walpole to Scott, James Watt shows the Gothic to have been a heterogeneous body of fiction, characterised at times by antagonistic relations between writers or works. He examines the novels' political import, and looks ahead to the fluctuating critical status of Scott and the Gothic.
Keywords: English fiction -- 18th century -- History and criticism.; Horror tales, English -- History and criticism.; English fiction -- 19th century -- History and criticism.; Gothic fiction (Literary genre), English -- History and criticism.; Gothic revival (Literature) -- Great Britain.; Politics and culture -- Great Britain.; Literary form -- History -- 18th century.; Literary form -- History -- 19th century.; Romanticism -- Great Britain.; Literary form.; Horror tales, English -- 18th century -- History and criticism.; Gothic fiction (Literary genre) -- Great Britain.; Horror tales, English -- 19th century -- History and criticism.; Roman anglais -- 18e siècle -- Histoire et critique.; Récits d'horreur anglais -- 18e siècle -- Histoire et critique.; Roman anglais -- 19e siècle -- Histoire et critique.; Roman gothique -- Grande-Bretagne.; Politique et culture -- Grande-Bretagne.; Romantisme -- Grande-Bretagne.; Genres littéraires.; Récits d'horreur anglais -- 19e siècle -- Histoire et critique.; Conflit culturel -- Grande-Bretagne -- Histoire -- 18e siècle.; Récits d'horreur anglais -- Histoire et critique.; Littérature frénétique -- Grande-Bretagne.; Genres littéraires -- Histoire -- 18e siècle.; Genres littéraires -- Histoire -- 19e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Gothic fiction (Literary genre); English fiction; Gothic fiction (Literary genre), English; Gothic revival (Literature); Horror tales, English; Literary form; Politics and culture; Romanticism; Great Britain; Gothic novel; Engels.; Gothic novel.; Gothic Revival (letterkunde); Letterkunde.; Littérature d'épouvante anglaise -- Grande-Bretagne -- Histoire et critique.; Roman gothique -- Histoire et critique.; Littérature fantastique -- 18e siècle.; 1700-1899; Electronic books.; Criticism, interpretation, etc.; History